Potential of Streptomyces sp. in preventing the in vitro growth of Colletotrichum acutatum, the causative agent of infection in Capsicum annum L. - Putri, Rochmalia Juniarti; Kawuri, Retno; Darmadi, Anak Agung Ketut; Narayani, Inna (Jurnal Biologi Udayana; Vol 25 No 2 (2021): JURNAL BIOLOGI UDAYANADO - 10.24843/JBIOUNUD.2021.v25.i02.p12, 2021)
Red chilli plant ( Capsicum annum L.) is one of the most popular vegetable crops in Indonesian society. One of them the pathogens attacks is Colletotrichum acutatum , a fungus causing anthracnose on red chilli. This study aims to determine the existence of Streptomyces sp. bacteria in the rhizosphere of the red chilli plant; the ability of Streptomyces sp. in inhibiting C. acutatum ; Minimum Inhibitory Concentration (MIC) of Streptomyces isolates extracts in inhibiting C. acutatum ; The Streptomyces isolation was carried out by dilution method using selective meida, namely Yeast Malt Agar. The Dual Culture method was used as an inhibition test between Streptomyces sp. and C. acutatum in vitro. A well diffusion method was used to test the effectiveness of the Streptomyces sp. and MIC filtrate concentration in inhibiting C. acutatum . The data obtained in this study were analyzed with Analysis of Varian (ANOVA) then continued with Duncan Multiple Range Test with 5% significance. Five Streptomyces isolates were found, namely Streptomyces sp.1, Streptomyces sp.2, Streptomyces sp.3, Streptomyces sp.4, and Streptomyces sp.5 in the rhizosphere of healthy C. annum L. plants in Daup Village, Kintamani District, Bangli Regency. Streptomyces sp. isolates. can significantly inhibit the growth of the fungus C. acuatum with inhibitory power ranging from 50.30% to 83.76%, Streptomyces sp.5 isolate was able to provide the highest percentage of inhibition in C. acutatum of 83.76 ± 2.91% with MIC 7% (v/v) with a diameter of 6.40 mm.